Exploring the impact of affect on the effectiveness of comparative versus non-comparative advertisements. Issue 2 (17th February 2019) - Wu, Linwan; Wen, Taylor Jing
ABSTRACT: Affect is important in advertising, but it has not attracted sufficient attention in the research of comparative advertising. Two studies were conducted to explore how affect influences the effectiveness of comparative versus non-comparative advertisements. Study 1 focused on context-induced affect and showed that participants with positive affect expressed more favourable attitudes toward a comparative advertisement than a non-comparative advertisement. Study 2 addressed the coexistence of context- and ad-induced affects. Results showed that in the condition of positive context-induced affect, participants liked a comparative advertisement more than a non-comparative advertisement when ad-induced affect was positive. However, they evaluated both types of advertisement similarly in a negative manner when ad-induced affect was negative. In the condition of negative context-induced affect, participants expressed more favourable attitudes toward the advertisement eliciting positive affect than the one eliciting negative affect (regardless of ad type). These studies provided theoretical and practical implications, as well as directions for future research.